Effect of Marine Water to Ward Betta Sp. Survival - Febriani, Anya Via; Khotimah, Khusnul; N., Nurman Kirat Al; Luthfi, Muhammad Jafar (Proceeding International Conference on Science and Engineering, 2020)
Betta fish (Betta sp.) Is a many fish which is traded as an ornamental fish at a price that is quite affordable in Indonesia. Habitat that is often found in betta fish is freshwater such as shallow waters, rice fields or tributaries. This study aimed to determine the effect of marine water giving on the survival rate of betta fish (Betta sp.). This research conducted at the Biology Laboratory of UIN Sunan Kalijaga, Yogyakarta in October 2019 with experimental research methods. The design used is RAL (Rancangan Acak Lengkap) with 5 treatments. The dose used is treatment with a dose of treatment A 0%, treatment B 25%, treatment C 50%, treatment D 75%, and treatment E 100% with maintenance for 6 days. Measured variables include life span, behavior (ethology), and water quality. The results showed that the life span of betta fish treatment A can live for 144 hours (still alive), treatment B can live for 144 hours (still alive), C treatment 8 hours 21 minutes, treatment D 2 hours 20 minutes, and treatment E 50 minutes. The observations of the treatment behavior A was calm, treatment B was active, treatment C was active, treatment D was aggressive, and treatment E was aggressive. Water quality used in the study is in the temperature range of 29o C-30o C and pH 6-8. The conclusion of this study is betta fish can survive at 25% marine water dose, while 50% -100% (absolute) treatment cannot survive, due to several factors.